The correlations between the TikTok application and the student learning outcomes - Maulidiniyah Maulidiniyah; Siti Quratul Ain (Himpunan Pengembang Kurikulum Indonesia, 2024)
In this era, social media users are not only adults, children have also played social media, such as TikTok, which contains video content. The use of TikTok for children, especially elementary school students, can have positive and negative impacts. The tendency of students to play TikTok for a long time causes a decrease in enthusiasm for learning and focus on learning. However, TikTok can be a learning medium that can increase student motivation. This study aimed to determine the relationship of TikTok application in learning with student learning outcomes. The research method used was quantitative, with a sample of 30 fourth-grade students of SDN 06 Belantik, Siak Sri Indrapura Regency. Data were collected through a questionnaire with 20 questions covering the use of TikTok and Pancasila learning motivation. Furthermore, data was analyzed using descriptive, normality, and linearity tests with the help of SPSS to calculate the data. The calculation results show that the use of TikTok social media for student learning shows a positive correlation, meaning a good relationship exists between the TikTok application and student learning outcomes. Abstrak Di era sekarang ini pengguna sosial media tidak hanya orang dewasa saja, anak-anak pun sudah bermain sosial media, seperti TikTok yang berisi konten-konten video. Penggunaan TikTok untuk anak-anak terutama siswa Sekolah Dasar dapat mengakibatkan ampak poitif dan negatif. Kecendurungan siswa bermain TikTok dalam waktu yang lama menyebabkan turunnya semangat belajar dan fokus dalam belajar. Namun, TikTok dapat digunakan sebagai media pembelajaran untuk meningkatkan motivasi siswa. Tujuan dari penelitian ini untuk mengetahui hubungan aplikasi TikTok dalam pembelajaran dengan hasil belajar siswa. Metode penelitian yang digunakan yaitu kuantitatif dengan sampel penelitian terdiri dari 30 siswa kelas IV SDN 06 Belantik Kabupaten Siak Sri Indrapura. Data dikumpulkan melalui kuesioner dengan 20 pertanyaan mencakup penggunaan TikTok dan motivasi pembelajaran Pancasila. Selanjutnya, dilakukan analisis data menggunakan uji deskriptif, normalitas, dan linieritas dengan bantuan SPSS untuk menghitung data. Hasil perhitungan menunjukkan bahwa penggunaan media sosial TikTok untuk pembelajaran siswa menunjukkan korelasi positif, artinya terdapat hubungan yang baik antara aplikasi TikTok dengan hasil belajar siswa. Kata Kunci: aplikasi TikTok; hasil belajar siswa; sosial media